P1241CALCIFICATIONS IN DIFFERENT VASCULAR BEDS ACROSS THE SPECTRUM OF CHRONIC KIDNEY DISEASE INCLUDING CALCIFIC UREMIC ARTERIOLOPATHY: ARE SKIN PUNCH BIOPSIES USEFUL?. (6th June 2020) - Roendbjerg, Anne Kristine; Rix, Marianne; Gyldenløve, Mette; Krustrup, Dorrit; Vejborg, Ilse; Lönn, Lars; Pasch, Andreas; Skov, Lone; Hansen, Ditte
Abstract: Background and Aims: Accelerated vascular calcification in different vascular beds is common in patients with chronic kidney disease (CKD). A severe form of vascular calcifications is calcific uremic arteriolopathy (CUA) presenting with painful ischemic skin lesions and high mortality. The prognostic value of skin biopsies in relation to CUA is unclear and the prevalence of skin vascular calcifications in different stages of CKD is sparsely described. The aim of the study was to describe the occurence of small vesssel vascular calcifications in unaffected skin biopsies in relation to calcifications in other vascular beds across the spectrum of CKD including CUA. Method: A cross-sectional cohort (total, n=39) comprising dialysis patients with current or previous CUA (CKD5D+CUA, n=9), dialysis patients without CUA (CKD5D-CUA, n=12), patients with CKD stage 3-4 (CKD3-4, n=12), and healthy kidney controls (control, n=6). The presence of vascular calcifications in the dermis and subcutis were assessed in 4 mm punch biopsies of unaffected skin from the lateral thigh. The presence of vascular calcification was evaluated by H&E, von Kossa and Alizarin staining. The presence of breast arterial calcifications (BAC) was evaluated by mammography, the abdominal aortic calcification score (AAC) by lateral lumbar X-ray and calcification propensity was measured by T50 reflecting the calcification propensity in blood. Results: None of the included patients showed vascular calcifications in skin biopsies. Declining kidney function was associated with presence of BAC, increased AAC and reduced T50 (Table). No significant difference was found between CKD5D+CUA and CKD5D-CUA regarding BAC (p=1.000), AAC (p=0.815) or T50 (p=0.165). CKD5D+CUA compared to all other groups had no difference in BAC (p=0.109) and AAC (p=0.141) but reduced T50 (p=0.004). Dialysis patients (CKD5D±CUA) had significant more BAC (p=0.003), higher AAC (p<0.001) and lower T50 (p<0.001). Conclusion: No vascular calcifications were found in punch biopsies from unaffected skin in patients with different stages of CKD including CUA. Despite imaging verified vessel calcification by BAC and AAC and increased calcification propensity by T50 . This suggest that conventional punch biopsies cannot be used to identify skin vascular calcification and thereby patients at risk for developing CUA.